The Legal Status of Appraisal of Materials Guarantee for Bancruptcy Process of Indonesia - Anne Rusiana; Jamal Wiwoho; Adi Sulistiyono (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
This research studies the legal status of a material guarantee for the bankruptcy process of Indonesia. The purpose of this research is to find out the legal status of whether the material guarantee that has been declared bankrupt by the appraisal because of not fulfill of repayment of the debtor to the creditor can be transferred on non-bankruptcy status? Moreover, what is the creditor’s execution rights to the debtor’s material guarantee? This research uses a normative legal research method, namely: legal research that is done with the purpose of discovering the principles and philosophical base (dogma or doctrine) of positive law, and the research of legal discovery efforts in concreto that is suitable to be implemented to solve a particular legal case. The result of this research is that material guarantees that have been determined as Bankruptcy cannot be transferred to their status when they are sold with a non-bankrupt status before a written decision by the judge justified the status. This shows obedience to the principles of legality and legal certainty, that selling the bankrupt assets with the status of (non-bankrupt assets) cannot be justified according to the law. If the curator still continues to sell the bankrupt assets, that process is illegal, including the execution of the selling according to the law. When it was being declared of bankrupt the total value of the material guarantee is assessed by the appraisal to be sufficient for paying all debts to the creditor, then it became the guarantee of repayment of the debtor, but if the value of the material guarantee valued by the appraisal is smaller than the debt, then there must be a reassessment in order to make justice for debtors and creditors. Mortgage-holding creditors, fiduciary guarantees, mortgage rights, mortgages, or other collateral rights, can execute their rights as if Bankruptcy did not occur, but there are several receivables that must be matched before executing their separatist rights.